Intravenous immunoglobulins: myth and reality - Tellier, Zera (Henry Stewart Talks, 2007)
The use of intravenous immunoglobulins (IVIg) as therapeutic proteins, Use of IVIg to provide effective treatment for autoimmune thrombocytopenic purpura, Use of IVIg in a large range of autoimmune or systemic inflammatory diseases, Increase in worldwide IVIg demand, Increased evidence showing the efficacy of IVIg, Mechanisms for the action of IVIg in autoimmune diseases, Need for classification of the recommendations for use, Clinical indications for IVIg therapy
Archived at 2021/02/25